Respuesta :

Here is the process I did:

2(6x+4)-6+2x=3(4x+3)+1

Step 1: Distribute the 2 to the numbers in the parentheses (6x +4) on the left side of the equation

6x(2)+4(2)-6+2x=3(4x+3)+1

12x+8-6+2x=3(4x+3)+1

Step 2: On the left side of the equation combine like terms

x's go with x's (12x and 2x):

(12x + 2x)+8-6=3(4x+3)+1

14x+8-6=3(4x+3)+1

normal numbers go with normal numbers ( 8 and -6):

14x+(8+(-6))=3(4x+3)+1

14x+2=3(4x+3)+1

Step 3: Distribute the 3 to the numbers in the parentheses (4x+3) on the right side of the equation

14x+2=4x(3) +3(3) + 1

14x+2=12x + 9 + 1

Step 4: On the right side of the equation combine like terms

normal numbers go with normal numbers ( 9 and 1):

14x+2=12x + (9 + 1)

14x+2=12x + 10

Step 5: Bring 2 from the left side to the right by subtracting it to both sides

14x+(2-2)=12x + (10-2)

14x = 12x + 8

Step 6: Bring 12x from the right side to the left by subtracting it to both sides

(14x - 12x) = (12x - 12x) + 8

2x = 8

Step 7: Isolate x by dividing 2 to both sides

[tex]\frac{2x}{2}  =\frac{8}{2}[/tex]

x = 4

Hope this helped!

Given equation is  one degree equation in x

Also it has only one variable 'x' hence it requires only one equation to solve for x  and the equation is given.

hence solution for x can be given as

2(6x+4)-6+2x =3(4x+3)+1

12x + 8 - 6 +2x = 12x + 9 + 1

12x +2 +2x =12x + 10

14x +2 = 12x +10

14x-12x = 10-2

2x = 8

x = 8/2= 4

for more information please refer to the link given below

https://brainly.com/question/1640242

ACCESS MORE